Cybersecurity and the future of agri-food industries - Okupa, Henry (My University, 2020)
The agri-food sector has been undergoing rapid changes in the areas of food production and distribution over the past decades. Over the years, the sector has moved from disconnected, independent and uncoordinated operations to a highly interconnected, dependent and coordinated operations that have enhanced efficiency. The principal cost of this highly efficient system of production is the increased complexity and the exposure to potential risks networked organizations face in the age of the fourth industrial revolution. Increasingly, the physical value of the agri-food sector’s activities has declined even as the intangibles (data, information, insights) have increased in value. As precision agriculture becomes the mainstream and global positioning systems and RFIDs are deployed to enhance traceability and safety, the importance of data protection and security also become exponentially critical to the integrity of the system. That the sector is ahead of the general economy in the adoption of autonomous machines and artificial intelligence implies that the crucial valuation in the sector would be on data generation, organization and analytics, and machine learning. The combined complexity of these systems and processes interacting together create value and at the same time exposes the industry to significant operational risks. For while it was much difficult for cows and grains of corn to be stolen, stealing the data supporting the value embedded in these commodities is becoming increasing easy and riskier. This research is an exploratory excursion into developing an awareness of the scope of the potential risks creeping into the agri-food sector. It raises concern about the nature, typology and structure of these cybersecurity risks, that identifies the skills and capabilities that are needed for the sector to continue producing value to its customers even as it sustains its competitiveness. It focuses attention on building the internal capacities along the agri-food supply chain to ensure that all stakeholders have the appropriate capabilities and capacities to address the impending and emerging challenges. After all, every chain is as strong as its weakest link. Cybersecurity threat has become a very critical challenge facing all businesses. And the agri-food sector is not immune to the threats it presents. Being prepared is a necessary condition for securing the sector’s future.
Keywords: Risk; Cybersecurity; agriculture; food